2003
DOI: 10.1017/s0016756803008112
|View full text |Cite
|
Sign up to set email alerts
|

Polymetamorphism and ductile deformation of staurolite–cordierite schist of the Bossòst dome: indication for Variscan extension in the Axial Zone of the central Pyrenees

Abstract: -The Bossòst dome is an E-W-trending elongated structural and metamorphic dome developed in Cambro-Ordovician metasedimentary rocks in the Variscan Axial Zone of the central Pyrenees. A steep fault separates a northern half-dome, cored by massif granite, from an E-W-trending doubly plunging antiform with granitic sills and dykes in the core to the south. The main foliation is a flat-lying S 1/2 schistosity that grades into a steeper-dipping slaty cleavage at the dome margins. Three major deformational and two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
62
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(89 citation statements)
references
References 53 publications
(76 reference statements)
6
62
0
9
Order By: Relevance
“…Clockwise PTt paths in the infrastructure have been documented from peak pressures of ca. 4.5 kb with significant heating during decompression and later cooling along a steep geotherm (Mezger and Passchier, 2003;Mezger et al, 2004;Mezger, 2005;Vilà et al, 2007). Recently, Aguilar et al (2015) reported metamorphic relicts suggestive of an early hightemperature peak pressure of 7.5 Kbar in the Roc the France dome (Fig.…”
Section: Pszmentioning
confidence: 91%
See 4 more Smart Citations
“…Clockwise PTt paths in the infrastructure have been documented from peak pressures of ca. 4.5 kb with significant heating during decompression and later cooling along a steep geotherm (Mezger and Passchier, 2003;Mezger et al, 2004;Mezger, 2005;Vilà et al, 2007). Recently, Aguilar et al (2015) reported metamorphic relicts suggestive of an early hightemperature peak pressure of 7.5 Kbar in the Roc the France dome (Fig.…”
Section: Pszmentioning
confidence: 91%
“…The northern sub-dome exposes a deep portion of the northern flank of the original dome, whereas the southern sub-dome exposes mostly the E-W elongate core and the southern flank of the original dome. Peraluminous granite sills are intercalated in the dome, particularly in its northern flank, which display mineralstretching lineations (Li) of two main trends (see also Mezger and Passchier, 2003). The dominant lineation is longitudinal, trending parallel or at a low angle to the map axis of the dome and a few transverse lineations are documented in the vicinity of the northern margin of the dome, sometime on the same outcrops than the longitudinal Li (see also Mezger and Passchier, 2003).…”
Section: The Bossost Domementioning
confidence: 97%
See 3 more Smart Citations